Antioxidant Activity Of Ethanol Extract And Ethyl Acetate Fraction Of Soursop (Annona Muricata) Leaves In Vitro - Marlita, Jeli; Sujono, Tanti Azizah (Jurnal Ners, 2024)
Antioxidants play an active role and are responsible for counteracting free radicals in the body through the process of inhibiting oxidation reactions. Secondary metabolite compounds of phenolic and flavonoid groups are compounds that are widely found in Annona muricata plants that have potential as antioxidants. The purpose of this study was to determine the antioxidant activity of soursop (Annona muricata) leaves using two methods, namely Ferric Reduction Antioxidant Power (FRAP) and 2,2-diphenyl-1-picrylhydrazyl (DPPH). The extraction method used is maceration method with 70% ethanol solvent, then fractionation using liquid-liquid extraction method, antioxidant test using DPPH and FRAP methods with measurement of levels using UV-Vis spectrophotometry. From the results of maceration, the yield of ethanol extract was 21% from 500 g dry simplisia of soursop leaves and the yield of ethyl acetate fraction was 32.78% from 50 g thick ethanol extract. The results of antioxidant activity test by FRAP method on ethanol extract and ethyl acetate fraction samples were 7.790 and 10.026 mgAAE/g, respectively. Both samples showed very strong antioxidant activity. In DPPH method, ethanol extract showed strong antioxidant activity with IC50 value of 63.947 µg/mL and ethyl acetate fraction showed very strong antioxidant activity with IC50 value of 6.702 µg/mL. From the results, it can be concluded that the ethyl acetate fraction showed very strong antioxidant activity in the DPPH and FRAP test methods, while the ethanol extract showed very strong antioxidant activity in the FRAP test method and strong antioxidant activity in the DPPH test method.